Knowledge about cervical cancer and HPV immunization dropout rate among Brazilian adolescent girls and their guardians - Ana Carolina da Silva Santos; Nayara Nascimento Toledo Silva; Cláudia Martins Carneiro; Wendel Coura-Vital; Angélica Alves Lima (BMC, 2020)
Abstract Background Infections with Human Papillomavirus (HPV) are the main cause of cervical cancer. Since 2014, the HPV vaccine was introduced in the Brazilian National Vaccination Calendar. The purpose of this study was to assess the knowledge of adolescent girls and their mothers/guardians about HPV and HPV vaccine, identify the factors associated with this knowledge, and evaluate immunization dropout rate. Methods This was a cross-sectional study involving adolescent girls and their mothers/guardians. Participants underwent an interview that addressed sociodemographic data, sexual and gynecological history, and knowledge about HPV, HPV vaccine and cervical cancer. The third quartile of the total score was established as a cutoff for assessing knowledge. Adolescents who correctly answered more than four questions and mothers/guardians who obtained more than five correct responses were categorized into high knowledge. Poisson regression analysis was performed to identify variables associated with low knowledge. Vaccination records were used to assess immunization dropout rates. Any adolescent who did not complete the two-dose vaccination schedule was considered dropout. Results A total of 666 adolescent girls and 623 mothers/guardians were interviewed. Low knowledge was observed in 76.7% of adolescents and 79.8% of mothers/guardians. Most were unaware of the causal relationship between HPV and cervical cancer, signs and symptoms of HPV infection, and had limited knowledge about the HPV vaccine. Factors associated with low knowledge of adolescents were aged 12 years [IRR 1.2 (95% CI 1. 1-1.3)] or less [IRR 1.3 (95% CI (1. 2-1.4)]; household income lower than US$750 [IRR 1.7 (95% CI 1. 1-2.6)] and household income between US$751 and US$1500 [IRR 1.6 (95% CI 1.0-2.6)]. Among mothers/guardians, low knowledge was related to having completed elementary school or less [IRR 1.5 (95% CI 1. 2-2.0)]; and household income lower than US$750 [IRR 1.2 (95% CI 1.0-1.4)]. Knowledge of adolescents and mothers/guardians was not associated with vaccine uptake. HPV immunization dropout rate was considered high (32.3%). Conclusion Knowledge about HPV and cervical cancer as well as vaccine uptake was low. Results highlight the need for educational interventions about HPV and cervical cancer. These actions may contribute to improve adherence to HPV vaccination.